Risk of Coinfection with Chlamydia trachomatis and Neisseria Gonorrhoeae in Nova Scotia - Kevin R Forward (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The frequency of Chlamydia trachomatis and Neisseria gonorrhoeae coinfection can vary depending on their individual incidence and prevalence rates.